Materials for Chemical Sensing - Cesar Paixão, Thiago Regis Longo; Reddy, Subrayal Medapati (Springer International Publishing : Imprint: Springer, 2017)
This book covers new materials used as analytical devices for increasing the interactions between the development of new analytical devices and materials science. The authors describe how different types of materials such as polymers, self-assembled layers, phthalocyanines, and nanomaterials can further enhance sensitivity and promote selectivity between analytes for different applications. They explain how continuing research and discussion into materials science for chemical sensing is stimulating the search for different strategies and technologies that extract information for these chemical sensors in order to obtain a chemical fingerprint of samples.